2004
DOI: 10.1161/01.res.0000132744.08754.f2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cardiac Myosin Binding Protein-C on Mechanoenergetics in Mouse Myocardium

Abstract: Abstract-We examined the effect of cardiac myosin binding protein-C (cMyBP-C) on contractile efficiency in isovolumically contracting left ventricle (LV) and on internal viscosity and oscillatory work production in skinned myocardial strips. A 6-week diet of 0.15% 6-n-propyl-2-thiouracil (PTU) was fed to wild-type (ϩ/ϩ PTU ) and homozygous-truncated cMyBP-C (t/t PTU ) mice starting at age Ϸ8 weeks and leading to a myosin heavy chain (MHC) isoform profile of 10% ␣-MHC and 90% ␤-MHC in both groups. Western blot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 43 publications
2
45
0
Order By: Relevance
“…Several investigators have proposed that the reduced unloaded shortening velocity in fiber studies is the result of cMyBP-C functioning either as a tether restricting myosin's interactions with actin [15,29,[43][44][45] and/or imparting a viscous load to thick-thin filament sliding [46]. Our data would indicate that neither of these mechanisms can account for the functional effects observed with cMyBP-C in this study.…”
Section: Discussionmentioning
confidence: 50%
“…Several investigators have proposed that the reduced unloaded shortening velocity in fiber studies is the result of cMyBP-C functioning either as a tether restricting myosin's interactions with actin [15,29,[43][44][45] and/or imparting a viscous load to thick-thin filament sliding [46]. Our data would indicate that neither of these mechanisms can account for the functional effects observed with cMyBP-C in this study.…”
Section: Discussionmentioning
confidence: 50%
“…This interpretation is well compatible with 2 recent studies on skinned myocyte Ca 2ϩ sensitivity. Whereas earlier studies had reported mixed effects of extraction or ablation of cMyBP-C on Ca 2ϩ sensitivity in skinned preparations (increase, 31,32 no change, 40 or decrease 25,29 ), the newer data on skinned KO preparations demonstrated a lower Hill coefficient of the pCa-force relation, indicating a reduced cooperativity of the myofilament activation. 27,31 A potential mechanistic explanation for this finding comes from a recent study describing a radial displacement of cross-bridges away from the thick filament in the absence of Ca 2ϩ .…”
Section: Discussionmentioning
confidence: 83%
“…Thus, it appears that ablation or phosphorylation of cMyBP-C result in similar accelerations in the rates of cross-bridge detachment, perhaps because of a decrease in a putative internal viscous load normally provided by cMyBP-C, which acts to slow the speed of shortening. 40 PKA phosphorylation of WT and cTnI ala2 myocardium also increased the number of cross-bridges that detach following stretch, which is evident in more negative values of P 2 ( Figure 3). Because more negative values of P 2 have been interpreted as indicating greater reversal of force-producing steps in response to stretch, 41 cMyBP-C phosphorylation appears to accelerate cross-bridge reverse transitions from strongly bound to weakly bound states so that force relaxation is accelerated.…”
Section: Discussionmentioning
confidence: 90%